Āṣtōttaraśatopaniṣatsu Sannyāsa-Upaniṣadaḥ : Upanisadbrahmayogiviracitavyākhyāyutaḥ ; Ṭi. Ār. Cintāmaṇidīkṣitena sampāditaḥ - Chintamani Dikshit, T. R.; Upaniṣadbrahmayogi (SAMP early 20th-century Indian books project ;, 1929)
Hindu philosophical classic; includes commentary by Upaniṣadbrahmayogi.